Double-sided tape coating and cutting process for flexible glass and flexible glass

CN122940376APending Publication Date: 2026-10-20WUHU DONGXIN PHOTOELECTRIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511847604.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-09
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]然而,经上述涂布处理后的柔性玻璃在切割环节易出现玻璃起角处崩边的现象,该现象对后续产品制作产生了诸多不利影响

Benefits of technology

[0016]本发明用于柔性玻璃的双面胶涂布与切割工艺,通过增加交联剂的用量,可以有效提高双面胶的交联密度,从而改善其内聚强度和粘附性能,同时采用等离子清洗机对双面胶表面进行预处理,等离子清洗机产生等离子体,设定等离子体的输出功率为第一阈值,高能粒子撞击双面胶表面,更高效地分解、剥离双面胶表面吸附的污染物,以显著提升双面胶的粘附力,提高生产效率与良率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
Patent Text Reader

Abstract

This invention discloses a flexible glass double-sided adhesive coating and cutting process and flexible glass. The process steps include: first, using a double-sided adhesive containing polyurethane adhesive and crosslinking agent to bond and fix the flexible glass to a glass base plate; then, applying a primer and a topcoat to the surface of the flexible glass and curing it to form a flexible glass assembly; subsequently, using a laser cutting machine to cut the edges of the assembly or to a predetermined size; and finally, peeling the flexible glass from the glass base plate. In this process, increasing the amount of crosslinking agent can improve the crosslinking density of the double-sided adhesive, optimizing its cohesive strength and adhesion performance; simultaneously, operating a plasma cleaning device at a first threshold power utilizes high-energy particles to decompose and remove contaminants from the surface of the double-sided adhesive, significantly enhancing the adhesion of the double-sided adhesive, ultimately improving production efficiency and product yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flexible glass technology. Specifically, this invention relates to a double-sided adhesive coating and cutting process for flexible glass and flexible glass itself. Background Technology

[0002] In the processing of flexible glass, in order to improve its surface properties and adaptability to subsequent processes, it is usually necessary to apply a thermosetting primer and topcoat.

[0003] However, flexible glass treated with the above coating is prone to edge chipping at the corners during the cutting process, which has many adverse effects on subsequent product manufacturing. For example, in the subsequent screen printing process, the chipped edges after cutting can lead to incomplete screen printing, resulting in a large number of defective products and seriously affecting production quality and efficiency. At the same time, the current cutting technology for this type of coated flexible glass is not yet perfect. When peeling after cutting, the chipping problem becomes more prominent, often requiring remedial measures such as changing the bonding substrate and cutting the lamination. This not only increases the complexity of the process but also raises production costs.

[0004] Furthermore, there are some unavoidable drawbacks when using laser cutting machines to cut flexible glass. On the one hand, the cutting accuracy of ultraviolet laser cutting machines is prone to fluctuations during the cutting process, and the precision of overflow varies, making it difficult to meet the requirements of high-precision processing. On the other hand, due to the characteristics of the double-sided adhesive used in the substrate, overflow and residue are easily generated at the cut site during the cutting process, which not only affects the appearance quality of the product but also interferes with subsequent assembly processes, leading to unstable product performance.

[0005] This invention provides a double-sided adhesive coating and cutting process for flexible glass, specifically addressing issues such as decreased cutting accuracy, peeling and detachment, and adhesive residue that occur when cutting and peeling flexible glass after thermosetting coating. The process aims to obtain products with no peeling and no adhesive residue, thereby improving production efficiency and yield. Summary of the Invention

[0006] This invention aims to at least solve one of the technical problems existing in the prior art. To this end, this invention provides a double-sided adhesive coating and cutting process for flexible glass, with the aim of improving production efficiency and yield.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is: a double-sided adhesive coating and cutting process for flexible glass, comprising the following steps: S1. Attach and fix the flexible glass to the glass base plate; S2. Apply primer and topcoat to the surface of flexible glass to form a coating on the surface of flexible glass. After curing, a flexible glass component is formed. S3. Use a laser cutting machine to cut the four edges of the flexible glass assembly to a predetermined size; S4. Separate the flexible glass from the glass base plate; In step S1, the flexible glass is fixed to the glass substrate by double-sided adhesive, which contains polyurethane adhesive and crosslinking agent; the power of the plasma cleaning equipment is set to a first threshold.

[0008] The total content of the polyurethane adhesive and the crosslinking agent accounts for 7%-15% of the double-sided adhesive.

[0009] The power of the plasma treatment is adjusted to be increased by 10%-50% based on the original power, and the treatment time is 30s-120s.

[0010] The crosslinking density of the double-sided adhesive layer is 2.5 × 10⁻⁶. 4 per μm 3 -4.0×10 4 The surface energy is 35mN / m-50mN / m.

[0011] The overflow amount in at least one edge region of the flexible glass is adjusted, specifically by reducing the overflow amount on at least one short side, in order to reduce the risk of overflow and detachment at the corner.

[0012] The overflow amount of the short side is reduced to 30%-70% of the original overflow amount, while the overflow amount of other edge areas remains at a fixed overflow amount.

[0013] The overflow of the short side is specifically reduced to 0.05mm-0.15mm, while the overflow of other edge areas remains at 0.2mm-0.4mm.

[0014] The present invention also provides a flexible glass, which is manufactured using the aforementioned double-sided adhesive coating and cutting process for flexible glass.

[0015] The peeling force of the flexible glass is 0.24 N / cm.

[0016] This invention relates to the double-sided adhesive coating and cutting process for flexible glass. By increasing the amount of crosslinking agent, the crosslinking density of the double-sided adhesive can be effectively increased, thereby improving its cohesive strength and adhesion performance. At the same time, a plasma cleaner is used to pre-treat the surface of the double-sided adhesive. The plasma cleaner generates plasma, and the output power of the plasma is set to a first threshold. High-energy particles collide with the surface of the double-sided adhesive, which more efficiently decomposes and peels off the contaminants adsorbed on the surface of the double-sided adhesive, thereby significantly improving the adhesion of the double-sided adhesive and increasing production efficiency and yield. Attached Figure Description

[0017] This manual includes the following figures, which illustrate the following: Figure 1 This is a schematic diagram illustrating the improvement of double-sided tape; Figure 2 This is a schematic diagram of the improved cutting process. Detailed Implementation

[0018] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings, in order to help those skilled in the art to have a more complete, accurate and in-depth understanding of the concept and technical solutions of the present invention, and to facilitate its implementation.

[0019] In a first aspect, embodiments of the present invention provide a double-sided adhesive coating and cutting process for flexible glass, comprising the following steps: S1. Attach and fix the flexible glass to the glass base plate; S2. Apply primer and topcoat to the surface of flexible glass to form a coating on the surface of flexible glass. After curing, a flexible glass component is formed. S3. Use a laser cutting machine to cut the four edges of the flexible glass assembly; S4. Separate the flexible glass from the glass base plate.

[0020] Specifically, the present invention aims to solve the problems of decreased cutting accuracy and peeling spillage of flexible glass products during peeling, thereby achieving flexible glass with no spillage and no residue.

[0021] In this embodiment of the invention, improvements were made to the double-sided adhesive: During actual testing and application, the inventors discovered that the peel force between the current polyurethane double-sided adhesive and the coating after applying primer and topcoat is relatively high. This problem causes the overflow portion around the double-sided adhesive to easily detach during the peeling process, leaving some adhesive residue, which not only affects the appearance of the product but may also adversely affect its performance and service life. To solve this problem, the inventors conducted in-depth research and experiments. First, the inventors adjusted and optimized the amount of crosslinking agent. By increasing the amount of crosslinking agent, the crosslinking density of the double-sided adhesive can be effectively increased, thereby improving its cohesive strength and adhesion performance. Second, the inventors adjusted the power of the plasma cleaner. Increasing the plasma power can more effectively treat the surface of the double-sided adhesive, improve its surface energy and activity, and enhance the adhesion between it and the coating. After multiple experiments and tests, the inventors found that through the above improvements, the peel force of the double-sided adhesive was significantly reduced, and its peel force was measured to be 0.24 N / cm. This result demonstrates that the improved double-sided tape is easier to peel off, with less excess tape around the edges during the peeling process, and the problem of residual adhesive is effectively solved. This not only improves product quality and reliability but also reduces scrap rates and maintenance costs during production.

[0022] Before using double-sided tape to adhere to flexible glass, the tape needs to be pre-treated to improve its adhesion. A plasma cleaner is used to pre-treat the tape surface. The plasma cleaner generates plasma, and the output power of the plasma is set to a first threshold. High-energy particles collide with the tape surface, more efficiently decomposing and peeling off contaminants adsorbed on the tape surface, thus significantly improving the tape's adhesion.

[0023] In this embodiment of the invention, the amount of crosslinking agent is adjusted to be 5%-20% higher by mass than the original amount. The addition of the crosslinking agent lays the foundation for improving the performance of the double-sided adhesive, as it can participate in subsequent reactions and help optimize the internal structure and performance of the double-sided adhesive. However, the crosslinking agent alone does not completely change the key issue of surface and coating adhesion; it must be combined with plasma treatment.

[0024] In step S1 above, the flexible glass is bonded and fixed to the glass base plate with double-sided adhesive. The double-sided adhesive contains polyurethane adhesive and crosslinking agent, and the total content of polyurethane adhesive and crosslinking agent accounts for 7%-15% of the double-sided adhesive.

[0025] In this embodiment of the invention, the plasma processing power is adjusted to be 10%-50% higher than the original power, and the processing time is 30s-120s. Increased plasma power enhances the etching effect of the plasma on the surface of the double-sided adhesive.

[0026] In this embodiment of the invention, the plasma output power is adjusted to 200W-300W, the processing time is 30s-120s, the gas is oxygen, and the flow rate is 50sccm-200sccm.

[0027] In this embodiment of the invention, the crosslinking density of the double-sided adhesive layer is 2.5 × 10⁻⁶. 4 per μm 3 -4.0×10 4 The surface energy is 35mN / m-50mN / m.

[0028] In this embodiment of the invention, the cutting process was also optimized: as a key step in the flexible glass coating production process, the quality of the cutting process directly affects the final performance and usability of the product. However, the current sample's cutting process has some shortcomings and needs optimization and improvement. In actual operation, the inventors found that because the current sample's cutting overflow around the edges is fixed, overflow at the corners is prone to detachment during peeling. This not only affects the product's appearance quality but may also cause the overflow to interfere with or damage other components. Further analysis revealed that the main reason for this problem is the relatively low peel force between the current polyurethane double-sided adhesive and the coating, resulting in insufficient fixation of the overflow during the cutting process. To address this issue, the inventors optimized the cutting process. First, the inventors reduced the overflow on one short side, thus reducing the risk of overflow detachment at the corners. At the same time, the overflow on the other sides remained fixed to ensure overall stability and reliability. Through this adjustment, the inventors successfully solved the overflow detachment problem, improving the product's appearance quality and consistency.

[0029] In step S2 above, after applying primer and topcoat to the flexible glass surface, the topcoat layer is placed on top of the primer layer, forming a coating on the flexible glass surface, and the coating is in contact with the double-sided adhesive.

[0030] In step S3 above, a UV laser cutting machine is used to cut the four edges of the flexible glass assembly to a predetermined size.

[0031] In step S4 above, after cutting is completed, the flexible glass with a coating on its surface is peeled off from the glass base plate to obtain the desired flexible glass product.

[0032] Flexible glass has two short sides and two long sides among its four edges. The two short sides are parallel, the two long sides are parallel, the long sides are perpendicular to the short sides, and the length of the short sides is less than the length of the long sides.

[0033] In this embodiment of the invention, the overflow amount of at least one edge region of the flexible glass is adjusted, specifically by reducing the overflow amount of a short side to reduce the risk of overflow and detachment at the corner.

[0034] In this embodiment of the invention, the overflow amount on the short side is reduced to 30%-70% of the original overflow amount, while the overflow amount in other edge areas remains at a fixed overflow amount, thereby improving the peeling yield and peeling effect.

[0035] In this embodiment of the invention, the overflow amount of the short side is specifically reduced to 0.05mm-0.15mm, while the overflow amount of other edge areas remains at 0.2mm-0.4mm.

[0036] Set the start and end points of the cut in areas where material spillage is unlikely. Cut one short side of the flexible glass first, then cut the remaining long and short sides to distribute stress at the corners. Avoid starting or ending the cut in stress-concentrated areas such as glass corners to reduce material spillage caused by sudden stress changes.

[0037] The above-mentioned double-sided adhesive coating and cutting process for flexible glass has the following advantages: (1) Improve product performance: By increasing the amount of crosslinking agent and plasma power, the peel force of double-sided tape is significantly reduced to 0.24 N / cm, making the peeling process smoother, reducing overflow and residue, improving product appearance quality and reliability, and enhancing user experience and satisfaction.

[0038] (2) Improve production efficiency and yield: Optimize the cutting process by reducing the overflow of the short side, solve the problem of overflow and fall off at the corner, improve the peeling yield, and at the same time, accurately control the cutting parameters and introduce automated equipment to improve cutting efficiency and accuracy, reduce scrap rate and cost, shorten the production cycle and enhance the company's market competitiveness.

[0039] Secondly, embodiments of the present invention provide a flexible glass, which is manufactured using the above-described double-sided adhesive coating and cutting process for flexible glass.

[0040] In this embodiment of the invention, the peel force of the flexible glass is 0.24 N / cm, making peeling relatively easy. The overflow is not easy to fall off, leaving no residue. The overflowing part at the edge does not fall off in the peel test.

[0041] The present invention has been described above by way of example with reference to the accompanying drawings. Obviously, the specific implementation of the present invention is not limited to the above-described manner. Any non-substantial improvements made using the inventive concept and technical solution; or the direct application of the inventive concept and technical solution to other situations without modification, are all within the protection scope of the present invention.

Claims

1. A double-sided adhesive coating and cutting process for flexible glass, characterized in that, Including the following steps: S1. Attach and fix the flexible glass to the glass base plate; S2. Apply primer and topcoat to the surface of flexible glass to form a coating on the surface of flexible glass. After curing, a flexible glass component is formed. S3. Use a laser cutting machine to cut the four edges of the flexible glass assembly to a predetermined size; S4. Separate the flexible glass from the glass base plate; In step S1, the flexible glass is fixed to the glass substrate by double-sided adhesive, which contains polyurethane adhesive and crosslinking agent; the power of the plasma cleaning equipment is set to a first threshold.

2. The double-sided adhesive coating and cutting process for flexible glass according to claim 1, characterized in that, The total content of the polyurethane adhesive and the crosslinking agent accounts for 7%-15% of the double-sided adhesive.

3. The double-sided adhesive coating and cutting process for flexible glass according to claim 1, characterized in that, The power of the plasma treatment is adjusted to be increased by 10%-50% based on the original power, and the treatment time is 30s-120s.

4. The double-sided adhesive coating and cutting process for flexible glass according to any one of claims 1 to 3, characterized in that, The crosslinking density of the double-sided adhesive layer is 2.5 × 10⁻⁶. 4 per μm 3 -4.0×10 4 The surface energy is 35mN / m-50mN / m.

5. The double-sided adhesive coating and cutting process for flexible glass according to any one of claims 1 to 3, characterized in that, The overflow amount in at least one edge region of the flexible glass is adjusted, specifically by reducing the overflow amount on at least one short side, in order to reduce the risk of overflow and detachment at the corner.

6. The double-sided adhesive coating and cutting process for flexible glass according to claim 5, characterized in that, The overflow amount of the short side is reduced to 30%-70% of the original overflow amount, while the overflow amount of other edge areas remains at a fixed overflow amount.

7. The double-sided adhesive coating and cutting process for flexible glass according to claim 6, characterized in that, The overflow of the short side is specifically reduced to 0.05mm-0.15mm, while the overflow of other edge areas remains at 0.2mm-0.4mm.

8. A flexible glass, characterized in that, The flexible glass is manufactured using the double-sided adhesive coating and cutting process for flexible glass as described in any one of claims 1 to 7.

9. The flexible glass according to claim 8, characterized in that, The peeling force of the flexible glass is 0.24 N / cm.